ONE-DAY WORKSHOP MEMBANGUN NILAI TRUST TERHADAP PRODUK LAYANAN PADA GENERASI Z DI METRO-LAMPUNG - Heri Satrya Wangsa, Ignasius; Josephine Tyra, Maria; Lina, Lina; Riyanto, Agustinus; Gunady Ony, Johan (Jurnal Abdimas Musi Charitas, 2023)
Digital service products require careful attention to the service delivery process and the establishment of trust value. The Community Service Team of Musi Charitas Catholic University Palembang conducted a workshop titled "Building Trust Value Towards Service Products for Generation Z in Metro - Lampung," involving 50 participants from Generation Z. The outcomes revealed that workshop participants were adept at illustrating trust value through three approaches: understanding the benefits of service products, recognizing the value that attracts purchasing interest, and perceiving the appealing benefits of products. The workshop received positive responses, with participants expressing a high level of understanding of the presented material and motivation to participate. Statistical analysis further confirmed the success of the activity in cultivating trust value perception among the participants.